Narrative transportability, leisure reading, and genre preference in children 9–13 years old. Issue 6 (1st November 2016) - Jensen, Jakob D.; Christy, Katheryn; Krakow, Melinda; John, Kevin; Martins, Nicole
ABSTRACT: Leisure reading behavior is a key predictor of educational success. Transportability is a trait that determines how likely an individual is to become involved in a story, and past research has suggested that involvement may be related to leisure reading behavior. However, available measures of transportability have not been validated with children or related to leisure reading. To address this gap, children 9–13 years old ( N = 136) completed a revised version of the Transportability Scale. A 13-item version of the scale was found to be unidimensional, reliable, and predictive of 6% of the variance in leisure reading (above and beyond sex, age, reading ability, and student performance). Transportability was also related to genre preference and several interesting sex differences emerged. The Transportability Scale provides researchers with a psychometrically sound measure of narrative involvement to advance research on leisure reading.